Optimasi Ekstraksi Kandungan Antosianin Total Bunga Telang Kering (Clitoria ternatea L.) Dengan Metode Microwave Assisted Extraction (MAE) - Riniati Riniati; Endang Widiastuti; Marisa Nursalsabila Ismail; Kevin Mochamad (Fluida, 2024)
Butterfly pea flower (Clitoria ternatea L.) has been used in Indonesia as a natural dye in food and cosmetics due to its varying colors, which depend on the acidity (pH) of the environment. The vibrant colors are attributed to the presence of anthocyanin compounds. This study optimized the anthocyanin extraction process from dried butterfly pea flowers using the Microwave Assisted Extraction (MAE) method. The variables tested included different concentrations of hydrochloric acid (HCl) at 0.01%, 1%, 2.5%, 3%, 3.5%, and 3.75% in 96% ethanol, as well as extraction times of 3, 6, 9, 12, and 15 minutes. The optimum extraction conditions identified were a HCl concentration of 3.5% in 96% ethanol with an extraction duration of 12 minutes, which yielded an anthocyanin concentration of 116.89 ppm.The FTIR analysis confirmed the similarity in functional groups between butterfly pea flower extracts and blackberry fruit extracts, highlighting the potential of butterfly pea flowers as a reliable anthocyanin source